THE STUDY SMART, SPEAK GLOBAL – JOURNEY OF INDONESIAN STUDENTS STUDYING ABROAD - Riance, Astri; Herlina, Herlina; Maryam, Eka (JURNAL UNIV.BI MENGABDI, 2025)
ABSTRACT The "Study Smart, Speak Global: Journey of Indonesian Students Studying Abroad" webinar is an inspiring event aimed at equipping young Indonesians with study abroad strategies, tips for improving their English skills, and firsthand experiences of Indonesian students abroad, helping them prepare for global competition and realize their dreams of studying internationally. This event aims to support Indonesian talent through international study, increase knowledge about studying abroad, and provide insights into college life abroad. The event focuses on effective study strategies (Study Smart) and improving English language skills (Speak Global) for global competition. This event was attended by university students from within and outside of Lubuklinggau who are interested in planning to study abroad. The resource persons for this event were Indonesian students with experience in studying abroad. Key words :Smart, Global, Journey, Aboard